Paclitaxel Through the Ages of Anticancer Therapy: Exploring Its Role in Chemoresistance and Radiation Therapy - Anna Maria Barbuti (Cancers, 2015)
Paclitaxel (Taxol®) is a member of the taxane class of anticancer drugs and one of the most common chemotherapeutic agents used against many forms of cancer. Paclitaxel is a microtubule-stabilizer that selectively arrests cells in the G2/M phase of the cell cycle, and found to induce cytotoxicity in a time and concentration-dependent manner. Paclitaxel has been embedded in novel drug formulations, including albumin and polymeric micelle nanoparticles, and applied to many anticancer treatment regimens due to its mechanism of action and radiation sensitizing effects. Though paclitaxel is a major anticancer drug which has been used for many years in clinical treatments, its therapeutic efficacy can be limited by common encumbrances faced by anticancer drugs. These encumbrances include toxicities, de novo refraction, and acquired multidrug resistance (MDR). This article will give a current and comprehensive review of paclitaxel, beginning with its unique history and pharmacology, explore its mechanisms of drug resistance and influence in combination with radiation therapy, while highlighting current treatment regimens, formulations, and new discoveries.